2022
DOI: 10.1097/jnr.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Experience of Immigrant Nurses in a Diverse Cultural Setting

Abstract: BackgroundWork-related stress (WRS) is one of the most common stressors in healthcare workplace settings.PurposeThis research study was designed to examine and discuss perceived WRS, job performance, social support, and the desire of immigrant nurses to work in a multicultural workplace.MethodsA case research mixed-methodology approach, a quantitative survey, and semistructured qualitative interviews were used in this research study. Three hundred twenty-one respondents were invited, of which 246 (76.6%) retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Psychological and Emotional effect on IENs -As IENs transition to their new surroundings, cultural norms, beliefs, and practices in the healthcare context, culture shock can have a significant, acute, and even chronic emotional impact. It can also cause feelings of disorientation and confusion [1,3,4,7,10,14,18,19,21,22,23,24,25,26,27]. 2.…”
Section: Defining Attributesmentioning
confidence: 99%
See 3 more Smart Citations
“…Psychological and Emotional effect on IENs -As IENs transition to their new surroundings, cultural norms, beliefs, and practices in the healthcare context, culture shock can have a significant, acute, and even chronic emotional impact. It can also cause feelings of disorientation and confusion [1,3,4,7,10,14,18,19,21,22,23,24,25,26,27]. 2.…”
Section: Defining Attributesmentioning
confidence: 99%
“…The lines of communication between IENs and their patients, coworkers, and other healthcare team members may be significantly impacted by this. [4,7,10,14,18,19,20,21,23,24,25,26,27,28,29,30,31, 32] 3. The availability of resources and support to the IENs-IENs must immerse themselves in the new healthcare system in order to find their new professional identity, resolve conflicts, and be able to acculturate.…”
Section: Defining Attributesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted with students come to the forefront in structuring the education curriculum. However, although there are studies in the literature examining nurses’ care experiences for individuals from different cultures (Hussam & Alnjadat, 2022; Sevinç, 2018), it was found that studies conducted with nursing students were primarily investigated using the quantitative method in the fields of cultural competence and effectiveness (Tosun, 2021; Üzar-Özçetin et al, 2020). No study has examined students’ experiences providing long-term nursing care to immigrants.…”
Section: Introductionmentioning
confidence: 99%